Effect of crossed magnetic field on ozone production in air - Buntat, Z.; Smith, I. R.; Razali, N. A. M. (Faculty of Electrical Engineering, 2009)
An application of magnetic field, B to a discharge chamber under transverse electric field, E is studied, with the objective to view the effect of magnetic field to the electrons in a plasma. Theory of gas discharge stated that this configuration will create a helical motion to electrons due to gradient drift or gyration. Experimental result from previous research showed, however that this magnetic field has no effect to corona current, in contrast to the theory that the helical motion will increase the ionisation collision process and cause more electron emissions. To verify the result, application of B effect to ozone chamber is constructed under AC and pulsed power supply, and the result shows that the B does not influence gas discharge characteristic agreeing with the result from previous author